Hubungan antara Tingkat Stres dengan Siklus Menstruasi pada Wanita Usia Produktif yang Bekerja di Dinas Kesehatan Kabupaten Bondowoso Tahun 2025 - Widyah Sariyantika; Muthmainnah Zakiyyah; Bagus Supriyadi (MUTIARA: Jurnal Ilmiah Multidisiplin Indonesia, 2026)
Menstruation is a physiological process experienced by women; however, disturbances in the menstrual cycle may increase the risk of reduced fertility among women of reproductive age. The prevalence of menstrual cycle disorders, which reaches approximately 45%, indicates a reproductive health issue that requires attention, particularly in relation to psychological factors such as stress. This study aims to analyze the relationship between stress levels and menstrual cycle regularity among reproductive-age women working at the Bondowoso District Health Office. A quantitative design with a correlational approach and cross-sectional method was employed, involving a population of 112 individuals and a sample of 53 respondents selected through random sampling. Data were collected using a standardized questionnaire and analyzed using the Chi-Square test. The results showed that the majority of respondents had normal stress levels, accounting for 25 individuals (47.2%), and normal menstrual cycles, accounting for 31 individuals (58.5%). Statistical analysis revealed a significant relationship between stress levels and menstrual cycle regularity with a p-value < 0.05, indicating that the research hypothesis was accepted. The findings confirm that stress levels are significantly associated with menstrual cycle regularity among working women. The novelty of this study lies in its specific focus on female workers in a regional health institution with distinct workload characteristics, providing empirical contributions to the development of stress management interventions aimed at maintaining women’s reproductive health.